Penciptaan Perempuan (Kajian Q.S.An-Nisa[4]:1) - Mir’atun Nisa (Syntax Corporation Indonesia, 2024)
The origin of women's creation cannot be separated from differences in interpretation and discussion in gender discourse. Based on Q.S.An-Nisa[4]: 1, this article aims to look back at the meaning of the verse from an ontological and axiological perspective. The method used in article writing is descriptive analytical. The theoretical framework is Hassan Hanafi's hermeneutic theory which consists of three criticisms, namely historical, eidetic and praxis. The result of the study is that Q.S. An-Nisa[4]:1 can be understood as the equality of the creation of man as a being who has a nafsio-physical unity. The ontologic implication is that women are self-made beings like men. Axiologically, women are no different from men in their roles because the relationship between men and women is equal and complementary.